Operando X-ray spectroscopic observations of modulations of local atomic and electronic structures of color switching smart film. Issue 22 (26th April 2017) - Lu, Ying-Rui; Wu, Tzung-Zing; Chang, Han-Wei; Chen, Jeng-Lung; Chen, Chi-Liang; Wei, Da-Hau; Chen, Jin-Ming; Chou, Wu-Ching; Dong, Chung-Li
Abstract : In situ / operando X-ray spectroscopic observation of color switchable smart film under gasochromic coloration. Abstract : Smart windows, which change color in response to external stimuli, are extensively studied owing to their potential technological applications in sensors and their ability to reduce the energy consumed by buildings. Most related studies focus on the optical properties of smart color switching films that can control the transmission of light and that of heat independently. This study examines the vanadium pentoxide thin film as a model system of a color switchable window. A gasochromic thin film of V2 O5 is fabricated using sol–gel spin coating. In operando soft X-ray absorption spectroscopy (XAS) at the V L-edge is used to determine the evolutions of the electronic and atomic structures of V2 O5 thin film under gasochromic color switching. Analysis of the V K-edge with respect to crystalline structural symmetry and valence requires many reference samples, whereas the V L-edge, which involves V 3d orbitals of various symmetries, can provide information about the atomic/electronic structures without many reference samples. A new gas reaction in situ cell was developed to collect the total-electron-yield XAS. The total-electron-yield signal can provide more accurate information about atomic and electronic structures than can the fluorescence-yield signal, which typically exerts a saturation effect. Analytical results reveal that the gasochromic reaction changes the charge state and causes a local atomic structural deformation of the film. The suggestion has been made that in the reaction, the central vanadium atom within the octahedron moves closer to the basal plane such that the apical V–O bond becomes more symmetrical than the film before gasochromic coloration. Unlike the cell that is used for hard XAS, and for which only cation sites can be studied, this in situ gas cell enables the real-time studies of atomic/electronic structures at gas–solid interfaces from viewpoints of both cation and anion sites.